The effect of CuO NPs on reactive oxygen species and cell cycle gene expression in roots of rice. (20th January 2015) - Wang, Shuling; Liu, Hanzhu; Zhang, Yuxi; Xin, Hua
Abstract: To evaluate the effect of CuO nanoparticles (NPs) on root growth, root reactive oxygen species (ROS) production, and the expression of 2 genes ( OsCDC 2 and OsCYCD ) associated with root growth of Oryza sativa (rice), rice roots were treated with 5 mg/L CuO NP suspension, 5 mg/L CuO bulk particle suspension, and 0.27 mg/L CuSO4 · 5H2 O solution, with distilled water as control. The results indicated that CuO NPs and Cu 2+ severely inhibited the elongation and biomass of rice roots after 72‐h exposure. Dyeing with 7′‐dichlorodihydrofluorescein–diacetate (DCFH–DA) showed that in all 3 treatment groups, the fluorescence was primarily located in the meristem zone, demonstrating that the meristem zone was where ROS were primarily generated. In addition, a significant increase in ROS was detected in the meristem zone of roots treated with the CuO NP suspension and the CuSO4 · 5H2 O solution, both of which greatly influenced the expression level of OsCDC 2 and OsCYCD . The impact of Cu 2+ on these 2 genes was smaller than that of CuO NPs. The Cu content in roots of rice after treatment with CuO NPs was much higher than that found after the other treatments, which indicated that CuO NPs may have been absorbed into root tissue. Collectively, these data suggest that growth inhibition, higher ROS production, and gene expression inhibition may be caused not only by the ions themselves, but also the NPs. Environ Toxicol Chem 2015;34:554–561. © 2014 SETAC